THU0367 INCIDENCE AND PREVALENCE OF SYSTEMIC SCLEROSIS-ASSOCIATED INTERSTITIAL LUNG DISEASE IN FLANDERS: A 12-YEARS COLLABORATIVE MULTICENTER PROSPECTIVE COHORT STUDY. (2nd June 2020) - Vandecasteele, E.; Melsens, K.; Blockmans, D.; Carton, C.; De Keyser, F.; De Langhe, E.; Lauwerys, B.; Piette, Y.; Vanhaecke, A.; Verbeke, K.; Wuyts, W.; Brusselle, G.; et al.
Abstract : Background: Systemic sclerosis-associated interstitial lung disease (SSc-ILD) is the main cause of death in SSc and accounts for up to 30-35% of SSc-mortality (1-2). All SSc cases, irrespective of the extent of the skin disease, should be evaluated for ILD (3). The epidemiology of SSc-ILD in Belgium is unknown. In literature, the prevalence of ILD in SSc varies between 19% and 52%. However, different criteria were used to diagnose ILD (4). In 2008, Goh et al. proposed a flow diagram to diagnose SSc-ILD based on chest high-resolution CT-scan (HRCT) and pulmonary function tests (PFTs). Their categorization into limited or extensive ILD has prognostic value (5). Objectives: To determine the prevalence and incidence rate of SSc-ILD in Flanders. Methods: Up to 12-year follow-up data of consecutive SSc patients were obtained by 2 Flemish expert centres (University Hospitals Ghent and Leuven). Patients fulfilling the LeRoy and/or ACR-EULAR classification criteria were included consecutively in the prospective cohort (6). Patients received HRCT at baseline and on indication thereafter, as well as yearly PFT. All HRCTs were centrally analyzed (Ghent) and patients were categorized according to the Goh criteria as without ILD, with limited ILD (limILD) or with extensive ILD (extILD) (5). Results: Between 2006 and 2018, 797 SSc patients (557 Ghent/240 Leuven; 22% limited SSc (LSSc)/59% limited cutaneous SSc (LcSSc)/19% diffuse cutaneous SSc (DcSSc)) had baseline HRCT and PFT. The baseline characteristics are depicted in the table. The mean age (SD) was 53 +/-15 years and the majority of patients was female (76%). 272 SSc patients had ILD at baseline, implicating a baseline prevalence of 34% (272/797). The baseline prevalences were 35% and 55% for the LcSSc and DcSSc subgroups respectively. During a median follow-up of 39 months (IQR: 11-79 months), 44 patients were diagnosed with incidental SSc-ILD, resulting in an incidence rate of 21, 0/1000 person-years (PY), 95% CI:15, 2-28, 1. The incidence rates were 21, 7/1000 PY, 95%CI: 14, 3-31, 6 and 43.9/1000PY, 95%CI: 22.7-76.8 for the LcSSc and DcSSc subgroups respectively. Conclusion: In an unselected cohort of SSc patients, a third of the patients has ILD at baseline which is in line with previous prevalence reports. Importantly, this is the first study reporting incidence rates of SSc-ILD. References: [1]Steen VD and Medsger TA, Ann Rheum Dis 2007;66:940-4 [2]Elhai M et al. Ann Rheum Dis 2017;76:1897-1905 [3]Smith V et al. RMD Open 2019;4:e000782. doi:10.1136/rmdopen-2018-000782 [4]Bergamasco A et al. Clinical Epidemiology 2019;11:257-73 [5]Goh N et al. Am J Respir Crit Care Med 2008;177:1248-54 [6]van den Hoogen et al. Arthritis Rheumatol 2013;65:2737-47 Disclosure of Interests: Els Vandecasteele Grant/research support from: my institution has received a research grant from the Research Foundation Flanders FWO), Speakers bureau: my institution has received speaker fees from Actelion, Karin Melsens: None declared, Daniel Blockmans Consultant of: yes, Speakers bureau: yes, Charlotte Carton: None declared, Filip De Keyser: None declared, Ellen De Langhe Consultant of: member of advisory board for Boehringer, Bernard Lauwerys: None declared, Yves Piette: None declared, Amber Vanhaecke: None declared, Koen Verbeke: None declared, Wim Wuyts Grant/research support from: my institution has received a grant from Boehringer Ingelheim and Roche, Consultant of: my institution has received payments for consultancy from Boehringer Ingelheim and Roche, Speakers bureau: my institution has received speaker fees from Boehringer Ingelheim and Roche, Guy Brusselle: None declared, Vanessa Smith Grant/research support from: The affiliated company received grants from Research Foundation - Flanders (FWO), Belgian Fund for Scientific Research in Rheumatic diseases (FWRO), Boehringer Ingelheim Pharma GmbH & Co and Janssen-Cilag NV, Consultant of: Boehringer-Ingelheim Pharma GmbH & Co, Speakers bureau: Actelion Pharmaceuticals Ltd, Boehringer-Ingelheim Pharma GmbH & Co and UCB Biopharma Sprl